Patterns of information management - Chessell, Mandy (M Press/ Pearson plc, 2013)
In the era of "Big Data," effective information management has become crucial to the success of virtually all organizations. Unfortunately, few IT practitioners know today's best practices for successfully managing enterprise information resources. "Patterns for Information Management" offers the solution: a multi-disciplinary patterns-based approach that reflects where information comes from, how it is distributed, protected, governed, monitored -- and, ultimately, utilized. Leading IBM information management experts Mandy Chessell and Harald Smith show how to design, integrate, and optimize "information supply chains" that: * Effectively characterize the information issues associated with today's complex distributed systems* Fully reflect today's service-oriented, message-based environments* Establish an information landscape that is effective, manageable, ordered, and efficient.* Create orderly flows of information which can be reused and synchronized wherever necessary* Support reasoned decision-making about the applicability and consequences of each alternative approach Chessell and Smith complement their plain-English information pattern language with a complete case study demonstrating its real-world applications. Their pioneering guidebook will serve as both an indispensable guide to architects at all levels of experience "and" an outstanding long-term information management reference.